1985
DOI: 10.1128/aem.49.3.637-643.1985
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal properties of a new water disinfectant

Abstract: The N-chloramine compound 3-chloro-4,4-dimethyl-2-oxazolidinone (agent I) has been compared with calcium hypochlorite as to its efficacy as a bactericide for the treatment of water. The study included concentration, contact time, pH, temperature, and water quality as controlled variables. The species of bacteria tested were Staphylococcus aureus, Pseudomonas aeruginosa, and Shigella boydii. In general, for highly pure, demand-free water, calcium hypochlorite was the more rapid disinfectant at a given total chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 11 publications
(8 reference statements)
2
30
1
Order By: Relevance
“…After incubation for 48 hours at 3TC, the plates were read for viable bacteria. The techniques used in these laboratories for microbiological analyses have been well documented (Williams et al, 1985. The aqueous solutions used to prewash the column were all prepared from distilled, deionized water that had been rendered chlorine-demand-free by prechiorination with 4 mg/i sodium hypochiorite followed by dechlorination in sunlight.…”
Section: Disinfection Studymentioning
confidence: 99%
“…After incubation for 48 hours at 3TC, the plates were read for viable bacteria. The techniques used in these laboratories for microbiological analyses have been well documented (Williams et al, 1985. The aqueous solutions used to prewash the column were all prepared from distilled, deionized water that had been rendered chlorine-demand-free by prechiorination with 4 mg/i sodium hypochiorite followed by dechlorination in sunlight.…”
Section: Disinfection Studymentioning
confidence: 99%
“…Chlorinated compounds have been used for disinfection purposes since the early 1900s due to their effective bactericidal action 1. They can act either as free small species, such as HOCl or NaOCl (which are considered to be the most effective disinfectants for water and clinical purposes),2–5 attached to amino containing compounds ( N ‐halamines), such as halogenated isoxazoles and halogenated imidazoles,6–11 or attached to high molecular weight compounds ( N ‐halamine polymers) 12–16…”
Section: Introductionmentioning
confidence: 99%
“…Agent I was synthesized and purified in the laboratory using the techniques of Kosugi et al (1976) as modified by Williams et al (1985). Calcium hypochlorite, obtained commercially (HTH; Olin Chemicals Corporation, New Haven, CT; 65% active chlorine, 35% inert ingredients), was used to chlorinate the precursor compound in situ.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in these laboratories have indicated the potential for using certain organic Nchloramines as broad spectrum disinfectants Worley et al 1981Worley et al , 1983aWorley et al , 1983bWorley et al , 1984aWorley et al , 1985Worley & Burkett 1984;Williams et al 1985). Of these compounds 3chloro-4,4-dimethyl-2-oxazolidinone, herein referred to as agent I, was first prepared and shown t o be bactericidal by Kaminski et al (1976) and by Kosugi et al (1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation